Имитационное моделирование внешних возмущений, действующих на упругую танковую пушку в канале вертикального наведения - Александров, Евгений Евгеньевич; Александрова, И. Е.; Пидашов, В. В.; Шматько, И. А. (НТУ "ХПИ", 2009)
In work the algorithm of modeling of external indignations which operate on a tank gun in the port of vertical prompting during tank movement on roads with a different covering and with different speeds is offered. The modeling example on one realization of "white noise" is resulted.
Keywords: танковая пушка; упругий ствол; система стабилизации; система наведения; математическая модель; возмущенное движение; вертикальное наведение; белый шум